Serum Biomarkers in Diagnosis and Clinical Management of Inflammatory Bowel Disease: Anything New on the Horizon - Ondriš, Juraj; Husťak, Rastislav; Ďurina, Juraj; Jurková Malicherová, Eva; Bošák, Vladimír (Folia biologica, 2024)
Persistent inflammation in inflammatory bowel disease (IBD) leads to progressive damage to the gastrointestinal tract, resulting in potentially severe sequelae. Diagnosis primarily relies on invasive endoscopy and monitoring of faecal calprotectin (FC), which has limitations, particularly regarding patient compliance. There is a pressing need for a new biomarker that is non-invasive, easily determinable, and possesses good diagnostic accuracy for both dia-gnosing and monitoring IBD. Our narrative review covers the latest developments in novel serum biomarkers, focusing on those with promising diagnostic accuracy and laboratory methods, and evaluates them in the context of established biomarkers such as FC and CRP. Serum calprotectin (SC) and leucine-rich alpha-2 glycoprotein (LRG) show the most extensive evidence and relatively good diagnostic accuracy but currently cannot replace FC due to insufficient evidence. Major limitations of the analysed studies include their monocentric nature, small sample sizes, lack of longitudinal monitoring and in some cases, missing assessments of endoscopic activity. ELISA holds a leading position among the laboratory methods; however, emerging evidence supports the potential use of point-of-care testing (POCT). Establishing these biomarkers for regular clinical application will require further validation through multicentric studies involving a larger number of patients with a longitudinal design, concurrent assessment of endoscopic activity and pro-active monitoring of the biomarker. However, based on the evidence accumulated so far, SC might potentially serve as a complementary biomarker and/or in assessing the activity of extraintestinal manifestations in IBD patients, while LRG appears to be effective in evaluating endoscopic activity, especially in small bowel CD.
Keywords: Feces; idiopatické střevní záněty; feces; biologické markery; Humans; Inflammatory Bowel Diseases; Leukocyte L1 Antigen Complex; lidé; Biomarkers; leukocytární L1-antigenní komplex